The Use Of Plastic Waste To Improve The Properties Of Clay Soil For Use In Paving Roads - Saeeda Omran Furgan; Rajaa Mohamed Sager (Green Publisher Indonesia, 2021)
The use of plastic materials such as polypropylene and poly ethylene has faced an enormous increase in the contemporary world. This factor of the contemporary world causes damage to the environment. The world wanted to reuse this waste in a productive way that reduces the ecological damage occurring to the environment. One of the best ways found after numerous researches to reuse this waste, is to utilise them in enhancing the properties of clay soil and further using it in paving roads. This paper focuses on the study that finds the use of plastic waste as the augmentation to improve the properties of soil and decrease the environmental pollution. The soil used in this paper is known to be expansive clay soil by AASHTO soil classification system.